2022
DOI: 10.1371/journal.pntd.0010814
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of serum extracellular vesicles identifies diagnostic markers for echinococcosis

Abstract: Echinococcosis is a parasitic disease caused by the metacestodes of Echinococcus spp. The disease has a long latent period and is largely underdiagnosed, partially because of the lack of effective early diagnostic approaches. Using liquid chromatography-mass spectrometry, we profiled the serum-derived extracellular vesicles (EVs) of E. multilocularis-infected mice and identified three parasite-origin proteins, thioredoxin peroxidase 1 (TPx-1), transitional endoplasmic reticulum ATPase (TER ATPase), and 14-3-3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…This protein is involved in endoplasmic reticulum membrane homeostasis and ubiquitination, and it has been detected in EV released from cancer cells 31 33 . Moreover, this ATPase was one of the three parasite-derived proteins found in serum EV from Echinococcus multilocularis -infected mice at different times after infection 34 . The authors describe this protein as a biomarker candidate for early diagnosis of echinococcosis.…”
Section: Discussionmentioning
confidence: 94%
“…This protein is involved in endoplasmic reticulum membrane homeostasis and ubiquitination, and it has been detected in EV released from cancer cells 31 33 . Moreover, this ATPase was one of the three parasite-derived proteins found in serum EV from Echinococcus multilocularis -infected mice at different times after infection 34 . The authors describe this protein as a biomarker candidate for early diagnosis of echinococcosis.…”
Section: Discussionmentioning
confidence: 94%
“…Such analysis could however be particularly useful in revealing novel facets of the pathological mechanisms associated with human strongyloidiasis, especially when applied in comparative studies. Indeed, this strategy has already been successfully applied to the study of other helminthiases, including schistosomiasis, fasciolosis and echinococcosis, to identify proteins or biological processes altered in the pathological state compared to uninfected controls, during the disease progression or in response to treatment [66][67][68][69][70][71][72][73][74][75][76]. The most commonly investigated samples are plasma/serum and plasma/serumderived EVs (either from animal models or from patients), even though also tissue proteomics has been described [69,70].…”
Section: Proteomics To Study the Host Response To The Infectionmentioning
confidence: 99%
“…The most commonly investigated samples are plasma/serum and plasma/serumderived EVs (either from animal models or from patients), even though also tissue proteomics has been described [69,70]. Importantly, a number of studies identified parasite proteins within the host's systemic or vesicular proteome, supporting the relevance of host proteomics also in revealing novel diagnostic markers [67,68,71,72,74,75]. Considering strongyloidiasis, many studies have investigated the systemic host response to the infection through the measurement of specific circulating factors, especially cytokines [11,[77][78][79][80][81][82][83].…”
Section: Proteomics To Study the Host Response To The Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, EVs are a resource with great potential [ 2 ], as these small lipidic vesicles of cellular origin are present in all biological fluids and have great stability. In fact, the potential of EVs as a source of disease-relevant biomarkers has been proposed for other parasitic pathogens [ 14 , 15 , 16 , 17 , 18 ]. EVs from Leishmania have been previously characterized [ 19 , 20 ] and parasite-associated proteins were also identified in infected macrophages [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%